Depressive symptoms in Type 1 and Type 2 Diabetes Mellitus and its relationship with glycemic control - Massano-Cardoso, Ilda Maria (2020)
Objective: The current study assessed depressive symptoms in Type 1 Diabetes Mellitus (T1DM) and Type 2 Diabetes Mellitus (T2DM) patients and explored whether these symptoms were associated with glycemic control. Methods: A cross-sectional design was used. Patients attending diabetes consultations participated in the study (N = 347). Participants completed the Beck Depression Inventory (BDI), and glycemic control was based on A1C criteria. Results: The mean score on the BDI, for either T1DM or T2DM, was not clinically significant and was not associated with diagnosis duration. The association between depression and glycemic control was significant in both DM types. T2DM participants presenting more depressive symptoms were those with greater glycemic control. T1DM and T2DM differences regarding depressive symptoms were in somatic symptoms. Conclusions: In T2DM depressive symptoms may be confounded with DM physical consequences. There is also the possibility that negative mood plays a mediating role in mobilizing survival strategies that promote glycemic control. Furthermore, the assessment of depressive symptomatology in patients with diabetes could benefit from the availability of a disease-specific measure.